Computed tomography and magnetic resonance imaging approaches to Graves’ ophthalmopathy: a narrative review - Luccas, Rafael; Riguetto, Cinthia Minatel; Alves, Monica; Zantut-Wittmann, Denise Engelbrecht; Reis, Fabiano (Frontiers in Endocrinology, 2024)
Graves' ophthalmopathy (GO) affects up to 50% of Graves' disease (GD) patients ranging from mild ocular irritation to vision loss. The initial diagnosis is based on clinical findings and laboratory tests. Orbital imaging, such as Magnetic Resonance Imaging (MRI) and Computed Tomography (CT), is an important tool to assess orbital changes, being also useful for understanding disease progression and surgical planning. In this narrative review, we included 92 studies published from 1979 to 2020 that used either MRI and/or CT to diagnose and investigate GO, proposing new methods and techniques. Most of the methods used still need to be corroborated and validated, and despite the different methods and approaches for TED evaluation, there is still a lack of standardization of measurements and outcome reports, therefore additional studies should be performed to include these methods in clinical practice, facilitating the diagnosis and approach for the treatment of TED.